The Impact of Natural Gas Prices on Electricity Tariffs in the UK - Mohammad Althaqafi (International Journal of Energy Economics and Policy, 2023)
The study was conducted to know the impact of natural gas prices on electricity tariffs in the UK. Although the United Kingdom doesn’t rely directly on Russian gas supplies, still, we are acutely vulnerable to the energy catastrophe that has resulted from the invasion of Ukraine. The UK is part of the European Union and that is a reason the UK energy tariff and natural gas prices are closely connected to the EU. The literature review will elaborate more on the impact of the natural gas price on electricity tariffs in the UK by using an unrestricted vector autoregressive (VAR) model. The historical data on natural gas prices have been collected from the official government website of the UK and from the ofgem website. The sample size was taken annually from January 2010 to August 2020. Our empirical study is close to (Mohammadi, 2009) who investigate the nexus between electricity prices and fossil fuel prices in the U.S economy.